Sensitivity of power spectral density techniques to numerical parameters in analyzing neutron noise experiments. (November 2017) - Gilad, E.; Geslot, B.; Blaise, P.; Dubi, C.
Abstract: Power spectral density (PSD) methods are well-known and widely used for the analysis of neutron noise experiments and obtaining the reactor's integral kinetic parameters, i.e., the effective delayed neutron fraction βeff and the prompt neutron generation time Λ . Many uncertainties are usually associated with PSD methods, e.g., statistical fluctuations in the neutron flux, power drifts, uncertainties in the Diven factor, the integral fission rate, and in the reactivity value. However, the uncertainty associated with the numerical parameters used in the power spectrum calculation procedure is hardly discussed in the literature and generally overlooked. The aim of this paper is to study the uncertainties in the kinetic parameters of a reactor core, obtained by PSD methods, which are associated with the numerical parameters of the method. A comprehensive estimation of the kinetic parameters, including all other uncertainties, is not pursued. In this paper, PSD methods are implemented to analyze critical and subcritical configurations of the MINERVE zero power reactor in order to measure its integral kinetic parameters β eff and Λ . Both cross and auto power spectral densities are calculated and the kinetic parameters are obtained via Lorentzian curve fitting over the calculated PSD. The sensitivity of the obtained kinetic parameters to the choice of numerical parameters used for spectrum calculations is studied and found to be significant with respect to other uncertainties. A novel methodology is proposed for analyzing the kinetic parameters' sensitivity to the PSD calculations and for quantifying the associated uncertainties. Highlights: Critical and subcritical configurations in MINERVE are analyzed using PSD methods. Sensitivity to numerical parameters used in power spectra calculations is studied. Uncertainty in integral kinetic parameter due to numerical parameters is calculated. New methodology for quantifying this sensitivity and associated uncertainty is proposed.